2006
DOI: 10.1590/s1413-35552006000300007
|View full text |Cite
|
Sign up to set email alerts
|

Redução do efeito analgésico da estimulação elétrica nervosa transcutânea de baixa freqüência em ratos tolerantes à morfina

Abstract: Objetivo: Investigar o efeito da TENS de baixa (10 Hz) e alta freqüência(130 Hz) aplicadas na pata inflamada do rato após tratamento crônico com morfina. Método: Foram utilizados 140 ratos Holtzman fêmeas, nos quais a carragenina (Cg 250 μg/0,1ml) foi administrada na pata posterior direita para a indução da inflamação. TENS de baixa e alta freqüência foi aplicada por 20 min, após 2 h e 30 min da Cg e seu efeito medido através do método de Randall-Selitto. O antagonista opióide Naltrexona (3mg/kg,sc), foi admin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 16 publications
(22 reference statements)
0
4
0
2
Order By: Relevance
“…On the other hand, some authors 21,22 have shown that TENS LF has induced analgesia by endogenous opioid release via µ receptor and that this could induce cross tolerance after prolonged opioid use. However, due to the type of experimental model proposed in this study, there were not enough data to observe such effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, some authors 21,22 have shown that TENS LF has induced analgesia by endogenous opioid release via µ receptor and that this could induce cross tolerance after prolonged opioid use. However, due to the type of experimental model proposed in this study, there were not enough data to observe such effect.…”
Section: Discussionmentioning
confidence: 99%
“…TENS LF action mechanism is not only the inhibition of spinal gates, but especially the activation of pain inhibitory descending system and modulation of the activity of transmission neurons located in spinal cord dorsal horn after endogenous opioids release. TENS LF effects are mediated by µ-type opioid receptors 4,21 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A estimulação elétrica pode trazer inúmeros benefícios quando indicada no controle da dor, pois, com a sua redução, o paciente aumenta o seu nível de função e atividade, pode participar de programas de exercícios físicos e melhorar a sua QV 12 . A estimulação elétrica nervosa transcutânea (TENS) tem como ação mais reconhecida a analgesia, que ocorre por meio de corrente elétrica de baixo limiar que inibe a transmissão dos estímulos dolorosos na medula espinhal e liberam opioides endógenos, como as endorfinas 13,14 . Silva e col. 15 realizaram ensaio clínico aleatório para avaliar os níveis de dor pela EAV, de QV pelo SF-36 e de depressão pelo Inventário de Beck, com 10 mulheres portadoras de FM com idade média entre 47 e 50 anos.…”
Section: Recursos Eletrotermofototerapêuticos E Fibromialgiaunclassified
“…According to the consensus on laser clinical trials 29 , studies must thoroughly describe the parameters of the intervention, such as wavelength, emitted energy, energy density, laser beam area, duration of application, peak power and density power 27 . The lack of a full description of parameters prevents the reproduction of the results, both in clinical and experimental settings.…”
Section: Tabe 1 Continuationmentioning
confidence: 99%